To the study of the spider fauna (Araneae) of the National Nature Park “Dvorichanskyi” - Полчанінова, Н. Ю. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
A checklist of 59 spider species found in the National Nature Park “Dvorichanskyi” is given.  Rare and protected species are provided with a brief characteristic of their geographical distribution.